Thermo-alkaline pre-treatment operated by digestate improved biomethane production of bioplastic. (February 2023) - Cucina, M.; De Nisi, P.; Adani, F.
Abstract: The present short communication reports the first attempt of digestate mediated thermo-alkaline pre-treatment of biodegradable bioplastics promoting biomethane production in a Circular Economy perspective. Two different commercial bioplastics were pre-treated at 90 °C for 72 h using anaerobic digestate as alkaline medium and they were then subjected to anaerobic digestion under thermophilic conditions (55 ± 2 °C). Digestate mediated pre-treatment enhanced significantly biomethane production from starch-based shoppers with respect to non-pretreated bioplastic (+30 %), whereas no significant differences were observed for biomethane production of polylactic acid bioplastic. Nevertheless, anaerobic digestion kinetic of polylactic acid was significantly improved by digestate mediated pre-treatment, probably due to the solubilization of the material during its pre-treatment that enhanced its biodegradability under anaerobic conditions. This promising bioplastics' pre-treatment should be further investigated to find the optimal pre-treatment conditions (i.e., temperature, duration) and to carry out a complete energetic assessment. Graphical abstract: Unlabelled Image Highlights: Bioplastics thermo-alkaline pre-treatment operated by digestate. Biomethane yield of starch-based bioplastic increased by 30 %. Kinetic of anaerobic digestion of PLA was enhanced by digestate pre-treatment. Digestate pretreatment reduced crystallinity of bioplastics promoting degradation. Ammonia favoured hydrolyzation of PLA into easy-degradable compounds.